(untitled) - Hill, Napoleon (New York, 2005)
In the original Think and Grow Rich, published in 1937, Hill draws on stories of Andrew Carnegie, Thomas Edison, Henry Ford, and other millionaires of his generation to illustrate his principles. In the updated version, Arthur R. Pell, Ph.D., a nationally known author, lecturer, and consultant in human resources management and an expert in applying Hill's thought, deftly interweaves anecdotes of how contemporary millionaires and billionaires, such as Bill Gates, Mary Kay Ash, Dave Thomas, and Sir John Templeton, achieved their wealth. Outmoded or arcane terminology and examples are faithfully refreshed to preclude any stumbling blocks to a new generation of readers.
Keywords: Thành công trong kinh doanh,Success in business